Painful shoulder syndrome and upper limb function in competitive swimmers - Pozarowszczyk-Kuczko, Beata; Kumorek, Martyna; Mroczek, Dariusz; Clemente, Filipe; Dziubek, Wioletta (Baltic journal of health and physical activity, 2024)
Introduction. Swimming is an athletic discipline that largely involves the upper limbs. Due to the driving and propulsive function, there is a heavy involvement of almost all muscles of the arm. Painful shoulder syndrome (PSS) is considered to be one of the main causes of interference with an effective and correct movement of the underwater stroke, which is a fundamental element of functionality in this discipline. The aim of this study was to evaluate whether PSS affects upper limb function in competitive swimmers. Material and methods. Thirty-two swimmers aged 17–24 years with at least 2nd sport class participated in the study. The swimmers were divided into two groups: group I – the experimental group, with subjects reporting pain in the shoulder area, and group II – the control group (sub-jects without pain in the shoulder area). Isokinetic tests at 60°/s, 180°/s, and 300°/s, hand grip strength tests, and upper limb power measurements on a swim er-gometer were performed. The standard visual analogue pain scale (VAS) was used to assess the severity of pain. Results. There were significant relationships between hand grip and pulling force. Hand grip also strongly correlated with peak torque in all considered limb movements. The other examined parameters did not show statistical significance. Conclusions. Despite the significant results of the study component, there was no significant in-fluence of painful shoulder syndrome on performance levels.